ANALISIS PENGARUH PENDEKATAN EXPERIENTIAL MARKETING TERHADAP KEPUASAN KONSUMEN (Studi Kasus pada Mahasiswa Pengunjung Perpustakaan S1 Reguler Ruang Referensi Fakultas Ekonomika dan Bisnis Universitas Diponegoro Semarang) - Rahmasari, Ika Agustina; Tri Astuti, Sri Rahayu (Diponegoro Journal of Management, 2013)
Experiential marketing is one of marketing strategies which relates products or services to the customer positively in some aspect. Not only limited to logic, but also to the emoticon and customer sense, so that products or services can be remembered more by customers. If it applied correctly, experiential marketing will  create customer satisfaction toward to  the  products or services. The purpose of this research to know the influence of the five dimensions of experientialmarketing to customer satisfaction in using products or services..Population of the research are the university students who visit the library of S1 Regular of Bussines and Economic Faculty Diponegoro University using purposive sampling method . Data collection is done using questionnaires. A quantitative analysis include validity and reliability, the classic assumption test, test hypotheses through F test and t test, coefficient of determination (R2). Data analysis techniques used were linear regression analysis. Qualitative analysis is the interpretation of the data obtained in this study.Hypothesis testing using t test showed that the five independent variables studied were Sense (X1), Feel  (X2), Think (X3), Act  (X4) and Relate  (X5) have significantly affect  to the dependent variable, Customer Satisfaction (Y). Then through the F test showed that the variables sense, feel, think, act, and relate have a significant effect together in customer satisfaction.